Is Anyone Listening? Variation in PSA Screening among Providers for Men 75+ before and after United States Preventive Services Task Force Recommendations against It: A Retrospective Cohort Study - Goodwin, James S. (Public Library of Science, 2014)
BACKGROUND: In 2008, the United States Preventive Services Task Force recommended against prostate specific antigen (PSA) testing for cancer screening in men age 75+. PURPOSE: To assess PSA screening by primary care physicians (PCPs) before and after recommendations. METHODS: In 2013, this retrospective cohort study analyzed PCPs in Texas with 20+ male patients aged 75+ in both 2007 and 2010, with Parts A and B Medicare. The main outcome was percent of PCP’s male patients 75+ who received PSA testing ordered by the PCP in 2007 and 2010, with no recent symptoms suggestive of prostate cancer. RESULTS: In both 2007 and 2010, 1,083 PCPs cared for at least 20 men aged 75 or older. The rate of PSA screening ordered by PCPs was 33.2% in 2007 and 30.6% in 2010. In multilevel analyses controlling for patient characteristics, the variation in PSA screening attributable to the PCP (intraclass correlation coefficient) increased from 23% in 2007 to 26% in 2010, p<0.001. Men with PCPs older than age 60 had 9% lower odds (95% CI, 1–17%) in 2010 compared to 2007 of receiving a PSA test, vs. a 4% increase (95% CI, 4% decrease to 12% increase) in men with PCPs aged 50 or younger. Patients with Board Certified PCPs had a 12% lower odds (95% CI, 8% to 16%) from 2007 to 2010, vs. 2% increase (95% CI 11% decrease to 18% increase) in men with PCPs without board certification. CONCLUSIONS: The USPSTF recommendation did not increase consensus among PCPs regarding PSA screening of older men.